1983
DOI: 10.1021/jf00118a030
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration mechanism of lemon flavor. 2. Formation mechanism of off-odor substances arising from citral

Abstract: 801some other Cg components, e.g., (Zl-6-nonenal or (2)-6nonenyl acetate, which were described by Buttery et al. (1982) to possess strong melon-like aroma far below the level of detection used in this study, seems probable.Registry No. , 95-16-9. LITERATURE CITEDAbd El-Baki, M. M.; A s h , A.; El-Samahy, S. K.; Abd El-Fadeel, M. G. Dtsch. Leben.sm.-Rundsch. Velluz, A.; Passerat, J.-P.; Ohloff, G. J. Sci. Food Renold, W.; Niif-Muller, R.; Keller, U.; Willhalm, B.; Ohloff, G. Schultz, T. H.; Flath, R. A.; Mon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 4 publications
2
103
1
Order By: Relevance
“…This alcohol undergoes a dehydration process and transforms to a, p-dimethylstyrene. Kimura et al [5] reported that a, p-dimethylstyrene and p-cymene were responsible for the off-odor of deteriorated lemon. In an oxygen environment, the end products of citral degradation consist of 80% a, p-dimethylstyrene and 8% cymene.…”
Section: Introductionmentioning
confidence: 99%
“…This alcohol undergoes a dehydration process and transforms to a, p-dimethylstyrene. Kimura et al [5] reported that a, p-dimethylstyrene and p-cymene were responsible for the off-odor of deteriorated lemon. In an oxygen environment, the end products of citral degradation consist of 80% a, p-dimethylstyrene and 8% cymene.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate compounds were selected from the list of components contained in lemon juice [9] or deteriorated lemon juice [10][11][12][13]. Unless the position on the 2-D map agreed exactly with those of the authentic components, the spots were recorded as unidentified.…”
Section: Identification Of Componentsmentioning
confidence: 99%
“…Thus, the presence of such alcohol components, not observed in fresh juice, may plausibly be due to the deterioration of some terpenic compounds under aqueous acidic conditions, common to lemon-flavored beverages. In order to identify these deterioration products, if present in the samples even without heat challenge, known deterioration compounds from citral [10][11][12][13] were injected and analyzed by GC6GC. The presence of pcymen-8-ol (s20), and p-methylacetophenone (s19) were confirmed.…”
Section: Components In Soft Drinks and In A Lowalcoholic Rtd Beveragementioning
confidence: 99%
“…HCI solution for 35 days. Kimura et al [9] studied the decomposition of citral in the presence of EtOH and citric acid and isolated acompound ('Peak 18') which was homogeneous on TLC and GLC, but which they considered to be a 1:l mixture of the ethoxy alcohols 10 and 11. A critical reevaluation of the reported spectroscopic data led us to the conclusion that the Japanese group actually had a single isomer in their hands since it displayed only 12 signals in the I3C-NMR spectrum and since the 'H-NMR signals for the EtO group are readily accounted for by analyzing this groups as an A M X , spin system with JRu = 9 Hz.…”
Section: Preparation Of Racemicmentioning
confidence: 99%
“…Kimura et a/. [9] stated that the diols were extremely unstable in acid and isolated what they considered to be a I : 1 mixture of the two ethoxy alcohols 10 and 11.…”
mentioning
confidence: 99%